Strengths and Difficulties Questionnaire (SDQ): Informant Agreement Between Children Born With Cleft Lip and/or Palate and Their Parents. (February 2018) - Bjerke, Susanna Memmen; Feragen, Kristin Billaud; Bergvik, Svein
Objective: Informant discrepancies on psychological measures may affect the assessment, classification, and treatment of children's mental health. Concordance between different informants has been shown to be low to moderately correlated. The present study examined the agreement between children with cleft lip and/or palate (CL/P) and their parents. Design: Cross-sectional data from 7 consecutive birth cohorts based on routine psychological assessments at age 10 with comparisons to national reference groups. Setting: Centralized and multidisciplinary treatment setting. Participants: 323 children age 10, born with CL/P and their parents (participation rate: 89%). Outcome measures: Strengths and Difficulties Questionnaire (SDQ). Results: Children born with CL/P and their parents tend to follow similar patterns of disagreement on the SDQ as reported in the general population, with children reporting more symptoms than their parents, and boys having more problems than girls on most subscales. Child and parent reports were low to moderately correlated, and not affected by the child's gender or the presence of conditions additional to the cleft. Conclusions: Differences between informants on the SDQ reflect different perspectives of the child's adjustment, and both informants are important in the assessment of mental health. Children with CL/P and their parents do not significantly differ from children and parents in the general population on their agreement of the child's psychological adjustment. As with the general population, clinical assessments should be based on a mixture of both informants' reports.